Analysis of available capitals in agricultural systems in rural communities: the case of Saraguro, Ecuador - Barrera-Mosquera, V.; de los Rios-Carmenado, I.; Cruz-Collaguazo, E.; Coronel-Becerra, J. (Spanish Journal of Agricultural Research, 2010)
This paper presents the application of a new methodology for the analysis and appraisal of capitals available in rural community farming systems in research, technological development and innovation (R&D&Ti) projects. The methodology is based on participatory processes in the appraisal of capitals and includes the following: a) analysis of objectives and classification by capital; b) design of variables and indicators; c) information collection and systemization; d) appraisal of indexes of community capitals; and e) analysis of capital indexes. The analysis was conducted in 19 communities in the Saraguro canton. These communities participated in an R&D&Ti project, which lasted for 14 years and is based on the Farming Systems Approach to Research. This application explains, for the first time in this region, the advantages of applying methods for appraising capitals available in community farming systems, considering the different dimensions that should be included in the implementation of the R&D&Ti projects for development. The principal contribution is based on the indexes of capitals and the appraisal that integrates information from the rural communities and their social preferences, using participative techniques in Farming Systems Research and in the processes of evaluation.